2007
DOI: 10.1007/s10562-007-9106-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenolysis of glycerol to propylene glycol on Cu–ZnO catalysts

Abstract: Hydrogenolysis of biomass-derived glycerol is an alternative route to sustainable production of propylene glycol. Cu-ZnO catalysts were prepared by coprecipitation with a range of Cu/Zn atomic ratio (0.6-2.0) and examined in glycerol hydrogenolysis to propylene glycol at 453-513 K and 4.2 MPa H 2 . These catalysts possess acid and hydrogenation sites required for bifunctional glycerol reaction pathways, most likely involving glycerol dehydration to acetol and glycidol intermediates on acidic ZnO surfaces, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
166
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(182 citation statements)
references
References 11 publications
8
166
0
8
Order By: Relevance
“…They also observed that addition of a phosphonium salts improved the selectivity and rate toward 1,2-propanediol. S. Wang & Liu (2007) converted glycerol to 1,2-propanediol on Cu-ZnO catalysts in temperatures between 180-240 o C and high hydrogen pressure 42 bar. They found that glycerol conversion and 1,2-propanediol selectivity depends on Cu and ZnO particle sizes.…”
Section: Propanediolsmentioning
confidence: 99%
“…They also observed that addition of a phosphonium salts improved the selectivity and rate toward 1,2-propanediol. S. Wang & Liu (2007) converted glycerol to 1,2-propanediol on Cu-ZnO catalysts in temperatures between 180-240 o C and high hydrogen pressure 42 bar. They found that glycerol conversion and 1,2-propanediol selectivity depends on Cu and ZnO particle sizes.…”
Section: Propanediolsmentioning
confidence: 99%
“…The hydrogenolysis of glycerol to propanediol is a promising option [1,2]. Until now, supported Cu [3], Co [4], Ni [5], Ru [6], Pt [7], Rh [8] and Ir [9] catalysts have been reported to be active towards glycerol hydrogenolysis. However, the sintering of the metal particles during the course of the reaction often resulted in catalyst deactivation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] In liquid-phase hydrogenolysis under hydrogen pressure, glycerol is converted into 1,2-PDO and 1,3-PDO in the presence of supported Rh, 5 Ru, [6][7][8]9 In the vapor-phase hydrogenolysis of glycerol, Cu catalyzes 1,2-PDO formation in the presence of high hydrogen pressure. [10][11][12][13] Since the hydrogenolysis requires elevated hydrogen pressure, 5-11 side reactions occur to form several by-products, including ethylene glycol (EG), propanol, lactic acid, and propanoic acid. Hydroxyacetone (HA) is an intermediate product in the conversion of glycerol into 1,2-PDO through the dehydration-hydrogenation reactions.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] In liquid-phase hydrogenolysis under hydrogen pressure, glycerol is converted into 1,2-PDO and 1,3-PDO in the presence of supported Rh, 5 Ru, [6][7][8] or Pt. 8,9 In the vapor-phase hydrogenolysis of glycerol, Cu catalyzes 1,2-PDO formation in the presence of high hydrogen pressure.…”
mentioning
confidence: 99%